Discovering Union Films and Its Archives - Musser, Charles (Cinémas, 2014)
This article begins by providing a narrative account of the (re)discovery of Union Films, the leading producer of left-wing documentaries in the United States in the immediate post-World War II era. Because of the Red Scare and blacklist, the organization has gone unmentioned in histories of documentary and radical filmmaking. The Orphan Film Movement has provided a cultural formation that has enabled this reclamation to unfold, providing a synergy between scholars, archives and labs. The question is then raised: where does the Union Films Project go from here?